2016
DOI: 10.1097/aud.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Speech-in-Noise Recognition From Performance on the Trail Making Test

Abstract: Short summary (100 words)The purpose of the study was to investigate the relation between performance on the Trail Making Test and speech-in-noise recognition. All tests were administered over the internet and a sample of 1509 adults aged between 18 and 91 years old was recruited. The results of the study indicate that better performance in the TMT is associated with better speech-innoise recognition scores. This association was not limited to the higher order processes indexed in the TMT-B test but was also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
4
24
1
Order By: Relevance
“…This result is consistent with the idea that the semantic priming effect obtained in the ignored condition was underlined by the shift in auditory attention from the attended channel to the ignored channel [47,63]. These results are in line with the idea that switching abilities are strongly involved and very useful during the processing of complex auditory scenes and in particular in speech-in-noise and speech-in-speech situations [34]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is consistent with the idea that the semantic priming effect obtained in the ignored condition was underlined by the shift in auditory attention from the attended channel to the ignored channel [47,63]. These results are in line with the idea that switching abilities are strongly involved and very useful during the processing of complex auditory scenes and in particular in speech-in-noise and speech-in-speech situations [34]. …”
Section: Discussionsupporting
confidence: 89%
“…Other executive components could be involved in SiS comprehension [34]. In a full three-factor model, EFs were described as a set of three components that all correlated with each other, i.e., updating, switching and inhibition [35].…”
Section: Introductionmentioning
confidence: 99%
“…Although previously theorized to load on separate cognitive abilities (Alloway et al, 2004) the result of our study does not support that notion. In a separate publication, we further analysed the relationship between the TMT and hearing ability in noise (Ellis et al, 2016). We found that processing speed accounted for a large portion of the contribution of the TMT in relationship to hearing performance, and that the "higher" cognitive functions that are loaded in the more complex TMT presentations have a very small, but significant, relationship to hearing performance.…”
Section: Figure 1correlational Heat Map Of All Items On the Haqmentioning
confidence: 95%
“…Thereafter, in the B part, numbers and letters are both included in the stimulus material and the participant is tasked with altering between symbols in the line drawing, thus making a line between 1 to A to 2 to B and so forth. In a separate publication, the optimal way of scoring this version in relation to hearing ability was determined to be the time it takes to complete the B version of the test (Ellis et al, 2016). Recruitment to the online screening was performed using advertisement in the national press.…”
Section: Studymentioning
confidence: 99%
“…The trail making test (TMT) was chosen as it has been shown that TMT measures executive functions such as task switching, which predicts relative difficulty in understanding accented speech in older adults [21] and young adults [22], as well as speech in noise recognition [23]. A TMT programme was written specifically to be administered on a touch-screen for the participants to carry out the test and to measure the time to complete the test more meticulously.…”
Section: Test Proceduresmentioning
confidence: 99%